PERMEABILITY FACTORS OF OFFICE BLOCK PEDESTRIAN ACCESS AT TRANSIT ORIENTED DEVELOPMENT AREA - KARET BENDUNGAN HILIR - Rikobimo Ridjal Badri; Nurhikmah B. Budi Hartanti (International Journal on Livable Space, 2021)
The development of public transportation in big cities in general, and Jakarta in particular, has set new trends in regional development by referring to the concept of Transit Oriented Development (TOD). Some superblock area development, bundled as a TOD area ignores several principles, especially pedestrian-friendly related values. Limited regulations and inconsistencies in understanding the application of TOD concepts and theories have resulted in the inappropriate application of TOD principles in transit-oriented areas. This study aims to find the implementation of connecting routes and the use of pedestrian paths with descriptive-qualitative methods by field observation. The research will be conducted in the Transit-Oriented development area Karet-Bendungan Hilir. The study shows that although the area being researched provides an ideal permeable block for pedestrian access, a problem with the management of the access prevents the pedestrian access to be fully functioning as a pedestrian networks system inside a Transit-Oriented Development area.